2020
DOI: 10.1002/jbm.a.37079
|View full text |Cite
|
Sign up to set email alerts
|

Hydrofluoric acid and nitric acid cotreatment for biofunctionalization of polyetheretherketone in M2 macrophage polarization and osteogenesis

Abstract: Due to its excellent mechanical and low‐friction properties, polyetheretherketone (PEEK) has been widely investigated for use in orthopedic applications over the past decade. However, the bioinertness and poor osteogenic properties of PEEK have hampered its clinical application. In this study, the surface of PEEK was modified by co‐treatment with hydrofluoric acid and nitric acid (AFN). The microstructures of the modified PEEK surfaces were investigated using scanning electron microscopy. The water contact ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The morphology of the biomaterial-seeded cells can also be examined by scanning electron microscopy (SEM) [ 14 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ], as well as the intracellular structures by transmission electron microscopy (TEM) [ 65 , 68 ]. Cell morphology and distribution can also be assessed using immunofluorescence staining of actin filaments, by means of anti-phalloidin antibodies among others, which allows for the analysis of the cytoskeleton conformation of cell growth in contact with the biomaterials [ 14 , 52 , 54 , 55 , 57 , 60 , 62 , 64 , 65 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Biomaterials Biocompatibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…The morphology of the biomaterial-seeded cells can also be examined by scanning electron microscopy (SEM) [ 14 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ], as well as the intracellular structures by transmission electron microscopy (TEM) [ 65 , 68 ]. Cell morphology and distribution can also be assessed using immunofluorescence staining of actin filaments, by means of anti-phalloidin antibodies among others, which allows for the analysis of the cytoskeleton conformation of cell growth in contact with the biomaterials [ 14 , 52 , 54 , 55 , 57 , 60 , 62 , 64 , 65 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Biomaterials Biocompatibilitymentioning
confidence: 99%
“…Fluorescent live/dead assays are able to discriminate between live and dead cells by evaluating plasma membrane integrity and the activity of the esterase enzyme, both maintained only in viable cells [ 54 , 55 , 60 , 62 , 70 , 74 , 75 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Other commercial colorimetric assays for the evaluation of cell viability are available on the market and, among the most widely used are the cell counting kit-8 (CCK-8) assay that allows a sensitive colorimetric measure of viable cells, using a water-soluble tetrazolium salt that produces, in presence of active dehydrogenases in living cells, an orange formazan product, and the amount of formazan produced is directly proportional to the number of viable cells [ 55 , 57 , 58 , 62 , 73 , 76 , 80 , 81 , 85 , 86 , 87 , 88 , 89 ]. Moreover, the Alamar Blue assay method is frequently used to assess the metabolic activity of proliferating cells: the active resazurin compound, upon entering living cells, is reduced to resorufin, a red fluorescent molecule that can be quantified [ 14 , 59 , 64 , 72 , 75 , 90 , 91 ].…”
Section: Biomaterials Biocompatibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Fukuda et al found that the plasma treatment and subsequent phosphorylation on the PEEK surface attenuated the phenotypic polarization of RAW264.7 macrophages to an inflammatory phenotype (Fukuda et al, 2019). A recent study revealed that PEEK modified with hydrofluoric acid and nitric acid could promote the polarization of macrophages (M2 phenotype) and inhibit the expression of proinflammatory factors via the NF-κB pathway (Huo et al, 2020).…”
Section: Modifications Inspired By Bone Immune Functionmentioning
confidence: 99%